Strategi Guru Pada Mata Pelajaran Bahasa Arab Dalam Membangkitkan Minat Belajar Siswa di MTS Nurul Afifah Aceh Tenggara - Gunawan, Adi; Hasan, Ibrahim (Journal of Student Development Information System (JoSDIS), 2024)
This study describes students' interest in learning, teachers' teaching strategies, and inhibiting factors in learning Arabic at MTs Nurul Afifah Aceh Tenggara. Qualitative methods were used through observation, interviews, and documentation. the results of this study show that1.) variations in students' interest in learning, with some showing high levels of enthusiasm, while others experience a lack of motivation. 2) Teachers apply diverse teaching strategies, including lectures, discussions and project-based learning to keep students engaged. 3)The inhibiting factors involve a lack of environmental support and limited awareness of the importance of Arabic.This study provides an in-depth insight into the conditions of Arabic language learning at MTs Nurul Afifah Aceh Tenggara. Conclusions highlight challenges and potential for development, with constructive suggestions to improve learning effectiveness and student interest.